Assessment of Small-Scale Microplastics Abundance and Characterization in Urban River: A Case Study in Metro River, Indonesia - Riyanto Haribowo; Prasetyo Rubiantoro; Arriel Fadhilah; Zefanya Alovy Petra Denindya; Yunike Ayu Kristanti; Wahyu Rismiati; Muhammad Aulia Arsal (Journal of Engineering and Technological Sciences, 2023)
Microplastic pollution is a pressing environmental concern with detrimental effects on aquatic ecosystems and human health. This study aimed to investigate microplastic contamination in a rapidly urbanizing area along a river and to examine the spatial distribution of microplastic abundance across the study area based on land use type. Seven sampling points were selected along the study site and microplastic samples were extracted using density separation and wet peroxidation (WPO) methods. The characteristics of the microplastic particles, including size, color, shape, and abundance, were analyzed to understand their properties. The results indicated that the microplastic abundance values ranged from 28.33 to 133.00 particles/liter, with an average of 73.55 particles/liter. Small microplastic particles (SMP), with sizes ranging from 1 μm to 1 mm, along with fragment shapes, and clear colors were predominant in the study area. A generalized additive model was utilized to assess the relationship between land use and microplastic abundance. The model demonstrated a significant influence of built-up areas on the presence of microplastics (p-value < 0.05), with an r2 value of 0.76. Residential areas near the river were identified as the likely primary sources of the microplastics.